Pemanfaatan Nangka Muda sebagai Bahan Isian Inovatif pada Produk Dimsum - Isnaini Nur Jannah; Alip Suroto; Denny Asmara (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The culinary sector continues to grow through product innovation and creative marketing strategies, supported by culinary tourism that increases tourists’ interest in tasting regional specialties. Indonesia has many potential local food resources, one of which is young jackfruit, which can be utilized as an innovative plant-based ingredient, although its use is still limited. This study aims to develop dim sum filled with young jackfruit as an innovative, healthy, and value-added product. A quantitative experimental method was used to objectively and measurably assess the quality and consumer acceptance of the dim sum. The formulation of the dim sum involved young jackfruit, eggs, tapioca flour, and wheat flour, through processes such as washing, boiling, chopping, and steaming. Sensory analysis results showed that sample B excelled in aroma, taste, and overall evaluation, while sample A had the best color, and sample C had the best texture. Some challenges identified included color changes due to oxidation, sap affecting taste, and high air content affecting texture if not properly drained. The final dim sum product had a light brown color, chewy texture, and was sensorially accepted as a high-quality dim sum with potential for further development as an innovative culinary product. These findings indicate that utilizing young jackfruit as a filling ingredient can be an attractive alternative in developing traditional processed foods with high nutritional value and consumer appeal.